MORPHOLOGY OF Ni-TiN/Si3N4 COMPOSITE COATINGS AT HIGH-TEMPERATURE OXIDATION - Budi, Esmar; Indrasari, Widyaningrum; Fahdiran, Riser; Nasbey, Hadi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
Electrodeposited nickel coating has excellent physical and mechanical properties, however it does not withstand to high temperature oxidation for long time. The addition of nitride phase within the nickel based coating improve the oxidation resistance through dense surface morphology improvement. A preliminary study was performed to investigate the high temperature oxidation behavior on the coating morphology after exposed at high temperature. The Ni-TiN/Si3N4 composite coatings deposited at electrodeposition temperature of 35 ℃, 40 ℃ and 50 ℃. The electrolyte consists of 0.17 M NiCl2.6H2O, 0.38 M Ni2SO4.6H2O, 6 g/L TiN, 0,6 g/L Si3N4, 40 g/L H3BO3, 0,6 g/L Sodium Dodecyl Sulfate (SDS). High temperature oxidation process on the samples was performed by heating at temperature of 700 ℃ for 2 hours within air conditions. The morphology and composition samples were characterized by using SEM/EDS. In general, the result showed that the morphology of Ni-TiN/Si3N4 composite coatings became rough due to the oxidation process. Elements coating such as Ni, Ti, Si and N were disappeared after the oxidation process due to the outward diffusion process.